The Manufacture and Characterization of Biomimetic, Biomaterial‐Based Scaffolds for Studying Physicochemical Interactions of Neural Cells in 3D Environments. Issue 2 (22nd February 2023) - O'Connor, Cian; Woods, Ian; Hibbitts, Alan; Dervan, Adrian; O'Brien, Fergal J.
Abstract: A particular challenge to the field of neuroscience involves translating findings from 2D in vitro systems to 3D in vivo environments. Standardized cell culture environments that adequately reflect the properties of the central nervous system (CNS) such as the stiffness, protein composition, and microarchitecture in which to study 3D cell–cell and cell–matrix interactions are generally lacking for in vitro culture systems. In particular, there remains an unmet need for reproducible, low‐cost, high‐throughput, and physiologically relevant environments comprised of tissue‐native matrix proteins for the study of CNS microenvironments in 3D. Advances in the field of biofabrication over the past number of years have facilitated the production and characterization of biomaterial‐based scaffolds. Typically developed for tissue engineering applications, they also provide sophisticated environments in which to study cell–cell and cell–matrix interactions and have been used for 3D modeling for a range of tissues. Here, we describe a simple and scalable protocol for the production of biomimetic, highly porous freeze‐dried hyaluronic acid scaffolds with tunable microarchitecture, stiffness, and protein composition. Furthermore, we describe several different approaches that can be used to characterize a range of physicochemical properties and how to employ the scaffolds for the 3D culture of sensitive CNS cells in vitro . Finally, we detail several approaches for the study of key cell responses within the 3D scaffold environments. Overall, this protocol describes the manufacture and testing of a biomimetic and tunable macroporous scaffold system for neuronal cell culture applications. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Scaffold manufacture Basic Protocol 2 : Scaffold characterization Basic Protocol 3 : Cell culture and analysis of neurons in scaffolds